2004
DOI: 10.1111/j.1439-0264.2004.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Nestin and IGF‐1 in Rat Pancreas after Streptozotocin Administration

Abstract: The present study examines whether centroacinar (CA) and intercalated duct (ICD) cells can serve as stem cells, after administration of the diabetogenic agent streptozotocin (STZ). Thirty rats were divided into five experimental groups: (1) control, (2) 1 day after STZ (STZ-1), (3) 3 days after STZ (STZ-3), (4) 7 days after STZ (STZ-7) and (5) 14 days after STZ (STZ-14). Many small pancreatic islets were observed in the STZ-7 group than in the other experimental groups, and many of these small islets were in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 23 publications
0
1
1
2
Order By: Relevance
“…Surprisingly, however, there was no nestin expression at all. This observation contrasts with the results of Nagasao et al [10] in STZ-treated neonatal rats. They found that 1% of the cells were nestin-positive 3 and 7 days after administration of STZ.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Surprisingly, however, there was no nestin expression at all. This observation contrasts with the results of Nagasao et al [10] in STZ-treated neonatal rats. They found that 1% of the cells were nestin-positive 3 and 7 days after administration of STZ.…”
Section: Discussioncontrasting
confidence: 84%
“…We expected to find a rise in expression of these transcription factors in the cells of all pancreatic compartments in association with concomitant c-Kit (CD117) and nestin expression. These two markers have been reported to be associated with pancreatic ducts and islets during pancreatic regeneration [6,10,12,21]. Finally, we wanted to gain insights into the different modes of regeneration in the pancreas of STZ-treated diabetic rats in comparison with other models.…”
Section: Introductionmentioning
confidence: 97%
“…Após a diferenciação, as células produziam insulina, glucagon, GLP-1 e PDX-1 (Zulewski et al, 2001). A nestina, no entanto, não está presente somente no pâncreas endócrino, mas também nos ductos (Nagasao et al, 2004). Estas célulastronco nestina-positivas também têm características de precursores de células β, com altos níveis de PDX-1 Nagasao et al, 2004).…”
Section: Células-tronco De Medula óSseaunclassified
“…A nestina, no entanto, não está presente somente no pâncreas endócrino, mas também nos ductos (Nagasao et al, 2004). Estas célulastronco nestina-positivas também têm características de precursores de células β, com altos níveis de PDX-1 Nagasao et al, 2004). Infelizmente, os estudos com células nestina-positivas foram descontinuados porque foi mostrado, em alguns estudos, que a nestina no pâncreas é expressa somente em células que não estão destinadas a tornarem-se células β (Treutelaar et al, 2003;Delacour et al, 2004;Street et al, 2004).…”
Section: Células-tronco De Medula óSseaunclassified